Testing a Water Redistribution Model in a Cracked Vertisol at Two Scales - Bagnall, D. (2020)
Water is preferentially conducted away from the soil surface through large cracks formed in shrink–swell soils, which complicates our ability to calculate the partitioning of water into infiltration and runoff. Preferential flow paths affect the hydrology of a landscape but often are not included in hydrology models. The Precision Agricultural‐Landscape Modeling System (PALMS) contains a Mesopore and Matrix (M&M) module that allows preferential flow and was tested on cracking soil at the pedon and small watershed scale for this study. Four irrigation events were conducted on 10‐m by 10‐m plots of a cracking soil, and volumetric water content (VWC) output for PALMS with and without the M&M module was compared with that measured by a neutron moisture meter. Additionally, measurements of VWC on a 4.4‐ha small watershed were compared with PALMS predictions. At both scales, the M&M module simulated water movement down the soil profile more quickly and eliminated unobserved ponding at the pedon scale relative to the PALMS matrix only. Simulations of water content of the soil profile were generally improved when the M&M module was used. Furthermore, PALMS M&M was relatively easy to parameterize using obtainable and physically relevant parameters, rendering it applicable to shrink–swell soils in a variety of systems.